Analisis Perlakuan Akuntansi terhadap Pembiayaan Musyarakah pada Bank Syariah Indonesia KCP Blangpidie Kuta Tuha - Dhea Anidar; Dewi Sartika (Universitas Teuku Umar, 2023)
This study analyzes the accounting treatment of Musyarakah financing at Bank Syariah Indonesia (BSI) KCP Blangpidie Kuta Tuha to determine whether implementing the Musyarakah contract at the BSI KCP Blangpidie Kuta Tuha is following PSAK No. 106. This study uses a qualitative descriptive research method using primary and secondary data sources collected through field observations, interviews with bank managers, and documentation. The results of this study indicate that the accounting treatment at BSI KCP Blangpidie Kuta Tuha regarding recognition, measurement, and disclosure follows PSAK No. 106. However, the accounting treatment related to the presentation is not tracking PSAK No. 106 because BSI presents cash and assets as musyarakah receivables, whereas based on PSAK 106, paragraph 35 states that cash or assets handed over to active partners are presented as musyarakah investments. BSI KCP Blangpidie Kuta Tuha is expected to be able to ensure the Musyarakah financing under PSAK No. 106.